Кіберфізичний підхід при створенні, функціонуванні та удосконаленні транспортно-виробничих систем - Аулін, В. В.; Гриньків, А. В.; Головатий, А. О.; Aulin, V.; Grinkiv, A.; Holovatyi, A.; Аулин, В. В.; Гринькив, А. В.; Головатый, А. О. (ЦНТУ, 2020)
Проаналізовано зміст кіберфізичного підходу до створення, функціонування та удосконалення транспортно-виробничих систем. На базі підходу створюються кіберфізичні транспортно-виробничі системи як інтеграція спеціальних технологій: Інтернет речей; вбудовані системи; повсюдні та хмарні обчислення. Визначено головні функції таких систем: обробка інформації, інтелектуальні комунікації, управління характеристиками і процесами. Побудована концептуальна схема та компонентна модель системи, яка включає дві групи компонент – еволюційну і технологічну. В еволюційну групу компонент входять підсистеми: цифрові; інтегровані; робототехнічні, розподілені інтелектуальні, а технологічна група є основою конкретних реалізацій Інтернет речей, вбудованих систем та повсюдних і хмарних обчислень. Запропоновано кіберфізичну систему технічного сервісу та визначено режими її функціонування. Виявлено наявність інтелектуальних моделей в кіберфізичній моделі технічного сервісу. The content of the cyberphysical approach to the creation, functioning and improvement of transport and production systems is analyzed. It was found out how, on the basis of the approach, cyberphysical transport and production systems are created as the integration of special technologies of the Internet of Things; embedded systems; ubiquitous and cloud computing. It was revealed that cyberphysical transport and production systems have a trinitarian concept and are defined by three entities: communication, computation and control, which unites information. It is determined that the main functions of cyberphysical transport and production systems are: information processing, intelligent communications, performance and process control. A component model of such a system has been built, which includes two groups of components - evolutionary and technological. The evolutionary group of components includes subsystems: digital; integrated; robotic, intelligent distributed. These components are a kind of basis for the presence of prerequisites for the creation of transport and production systems. It is noted that the technology group of components is the basis for concrete implementations of the Internet of Things, embedded systems and ubiquitous and cloud computing. A cyberphysical system of technical service is proposed as a specific implementation of cyberphysical transport and production systems. It was determined that the modes of the proposed functional cyber system are: high adaptability; an appropriate level of efficiency; intelligence of management; high level of reliability; the use of a new on-net online simulation type; using a new type of self-verifying models; internal online optimization, etc. It is shown that the presence of intelligent models in the cyberphysical model of technical service makes the system resistant to cyberattacks and increases the degree of safety when ensuring traffic in transport and the development of an occupational safety system during maintenance and repair operations. Проанализировано содержание киберфизического подхода к созданию, функционированию и совершенствованию транспортно-производственных систем. На базе подхода создаются киберфизические транспортно-производственные системы как интеграция специальных технологий Интернет вещей; встроенные системы; повсеместные и облачные вычисления. Определены основные функции таких систем: обработка информации, интеллектуальные коммуникации, управления характеристиками и процессами. Построена концептуальная схема и компонентная модель системы, которая включает две группы компонент - эволюционную и технологическую. В эволюционную группу компонент входят подсистемы: цифровые; интегрированные; робототехнические, распределены интеллектуальные, а технологическая группа является основой конкретных реализаций Интернет вещей, встроенных систем и повсеместных и облачных вычислений. Предложено киберфизическую систему технического сервиса и определены режимы ее функционирования. Выявлено наличие интеллектуальных моделей в киберфизической модели технического сервиса.
Cyberphysical Approach to the Creation, Operation and Improvement of Transport and Production Systems
Киберфизический подход при создании, функционировании и совершенствовании транспортно-производственных систем
Keywords: кіберфізичний підхід; транспортно-виробнича система; компонентна модель; технічний сервіс; cyberphysical approach; transport and production system; component model; technical service; киберфизический подход; транспортно-производственная система; компонентная модель; технический сервис